Opening a new route into home ownership? The extension of the Right to Buy to housing associations in England. Issue 2 (2nd April 2020) - Pattison, Ben; Cole, Ian
Abstract: The introduction of the mandatory 'Right to Buy' (RTB) in 1980 for qualifying tenants in municipal housing was a significant development in British housing policy. It was an extension of the post-war 'social project' of the state-subsidised expansion of home ownership, leading to the sale of nearly two million dwellings over forty years. In 2015, the UK government sought to 'reinvigorate' RTB by extending it to the housing association (HA) sector in England, initially on a pilot basis. This article investigates the impact of this pilot programme and the response of eligible tenants to the opportunity to purchase. It compares the pilot programme to the local authority RTB in terms of the changing demographic base of social renting, increased spatial differentiation in the housing market, the different institutional framework for HAs and the design of the pilot scheme. Research findings suggest that the take-up and impact of any national RTB scheme is likely to be limited, for a mixture of financial, institutional and demographic reasons. RTB will provide only a very selective route into home ownership for some HA tenants, as a specific segment of a more fragmented tenure than in 1980.